The critical probability for Voronoi percolation in the hyperbolic plane tends to 1/2. Issue 1 (11th May 2021) - Hansen, Benjamin T.; Müller, Tobias
Abstract: We consider percolation on the Voronoi tessellation generated by a homogeneous Poisson point process on the hyperbolic plane. We show that the critical probability for the existence of an infinite cluster tends to 1/2 as the intensity of the Poisson process tends to infinity. This confirms a conjecture of Benjamini and Schramm [5].